Productive and reproductive parameters in high and low growing Syrian Awassi lambs (Acta Scientiarum. Animal Sciences, 2018)
The objective of this study was characterize some productive and reproductive parameters in Syrian Awassi ewe lambs during different age stages. Thirty Syrian Awassi ewe lambs aged around 3 months were divided equally into 2 groups, high and low growing to identify productive and reproductive parameters during different stages. Blood samples were collected to determine progesterone and leptin concentrations. Daily milk samples were collected to determine the average daily production. At puberty, average body weight of higher growing was higher (48.4 kg) than de crescimento low growing (42.8 kg). Average age at puberty was 359.5 and 394.9 days for high and low groups, respectively with no differences. Mating, lambing and fecundity rates were similar among groups. Progesterone concentration was very low and increased rapidly at puberty with a sharp increase during pregnancy, followed by a noticeable decrease post lambing. There were individual variations in leptin concentration with no clear trend in groups. Average leptin concentration at puberty was 2.42 and 2.50 ng mL-1 for higher and low groups, respectively with no difference. Average daily milk production was higher for the higher group (1.495 g day-1) compared to 1.077 g day-1 for low grups. Thus, the lambs growing alter produtive and reproductive parameters.